2014
DOI: 10.1186/1476-4598-13-197
|View full text |Cite
|
Sign up to set email alerts
|

Malignancy-associated metabolic profiling of human glioma cell lines using 1H NMR spectroscopy

Abstract: BackgroundAmbiguity in malignant transformation of glioma has made prognostic diagnosis very challenging. Tumor malignant transformation is closely correlated with specific alterations of the metabolic profile. Exploration of the underlying metabolic alterations in glioma cells of different malignant degree is therefore vital to develop metabolic biomarkers for prognosis monitoring.MethodsWe conducted 1H nuclear magnetic resonance (NMR)-based metabolic analysis on cell lines (CHG5, SHG44, U87, U118, U251) deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
58
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 45 publications
2
58
0
1
Order By: Relevance
“…The NMR spectra were gathered in the NMR spectrometer (Bruker AVANCE III 600 Hz HD; Bruker BioSpin, Germany) with TXI probe at 298 K. The NOESYPR1D pulse ([RD‐90°‐t 1 ‐90°‐τ m ‐90°‐acq]) was applied to the process of acquirement. The detailed parameters of acquired process were referred to the previous works …”
Section: Methodsmentioning
confidence: 99%
“…The NMR spectra were gathered in the NMR spectrometer (Bruker AVANCE III 600 Hz HD; Bruker BioSpin, Germany) with TXI probe at 298 K. The NOESYPR1D pulse ([RD‐90°‐t 1 ‐90°‐τ m ‐90°‐acq]) was applied to the process of acquirement. The detailed parameters of acquired process were referred to the previous works …”
Section: Methodsmentioning
confidence: 99%
“…Recently, metabolomics studies indicated that “metabolic phenotypes” possess great potential for development of novel therapeutics and monitoring of treatment response in brain tumors . Therefore, a relevant number of studies focus on the metabolic characterization of immortalized and primary isolates or cultured cells which include neurones, glial cells, astrocytes, and neural stem cells and their benign and malignant counterparts . Updated lists of the metabolic alterations in adult and paediatric brain tumors associated with neuroblastoma, GBM (low and high grade gliomas), meningioma, and other rare malignant brain tumors are reported in Tables and .…”
Section: Metabolomics Studies In Adult Brain Tumorsmentioning
confidence: 99%
“…Detection and targeting of miss-regulated choline-, myo-inositol-, creatine-, and glycine-metabolism has been de scribed to have potential utility in the diagnosis and treatment of malignant gliomas [2][3][4]13,16,19]. This is, to our knowledge, the hitherto first link of changes in those oncometabolites [4,25] to variations in cell culture conditions of glioma cells. Interspectral co-analysis of metabolite concentrations under the two propagation conditions identified reductions in ratios of phosphocholine to glycerophosphocholine (PC/GPC) and glycine to total choline (Gly/tCho) but increases in the quotient of total choline to total creatine (tCho/tCre) and PC/tCre, as well as Gly/myo-inositol (Gly/myo).…”
Section: Communicating Authormentioning
confidence: 99%